"Tell me how you read and I will tell you who you are": children's literature and moral development - Van der Nest, Megan (Rhodes University, Faculty of Humanities, Department of Philosophy, 2010)
It is a common intuition that we can learn something of moral importance from literature, and one of the ways in which we teach our children about morality is through stories. In selecting books for children to read a primary concern is often the effect that the moral content of the story will have on the morality of the child reader. In this thesis I argue in order to take advantage of the contribution that literature can make to moral development, we need to teach children to read in a particular way. As a basis for this argument I use an account of moral agency that places emphasis on the development of moral skills - the ability to critically assess moral rules and systems, and the capacity to perceive and respond to the particulars of individual situations and to choose the right course of action in each - rather than on any particular kind of moral content. In order to make the most of the contribution that literature can make to the development of these skills, we need to teach children to immerse themselves in the story, rather than focusing on literary criticism. I argue that, contrary to the standard view of literary criticism as the only form of protection against possible negative effects, an immersed reading will help to prevent the child reader from taking any moral claims made in the story out of context, and so provide some measure of protection against possible negative moral effects of the story. Finally I argue that there are certain kinds of stories - recognisable by features that contribute to a high literary quality - that will enrich the experience of an immersed reading, and will therefore make a greater contribution to moral development than others.
Keywords: Children's literature -- Philosophy; Children's literature -- Moral and ethical aspects; Children's literature -- History and criticism; Literature and morals; Ethics in literature; Reader-response criticism; Moral conditions in literature; Literature -- Study and teaching